Kajian Metode Dakwah untuk Anak Berkebutuhan Khusus - Syakur, Abd.; Adawiyah, Siti Aisyatul; Zuhri, Syaifudin (Proceedings of International Conference on Da'wa and Communication, 2019)
The problem of this research is about the da’wah method of Ustadzah Rina to deaf-mute children at SLB Dharma Wanita Lebo, Sidoarjo, in 2019. The formulation of the problem was identified by researchers using qualitative research with a descriptive approach. Data collection techniques in this research used are observation, interviews, and documentation. The data analysis technique uses the Miles and Huberman models. The result and conclusion of this research is: the da’wah method of Ustadzah Rina to deaf and mute is bi al-hal method with evaluation techniques of daily life that researchers named Life Experience Debate. This is a new thing that researchers have not found used by da’i, especially for mad’u who have hearing obstacles (deaf). Ustadzah Rina through the daily activity book called the Life Experience Debate technique tries to give message understanding for deaf people with their limitations. Learning from previous experiences so they can change bad behavior for the better.